Project-Based STEM (Science, Technology, Engineering, and Mathematics) to Improve Critical Thinking Skills and Science Literacy - Meita Lilis Sitompul; Lenni Sitanggang; Ade Syafrina; Romince Simatupang; Dinda Amelia Lubis; Sugiharto; Sriadhi (Jurnal Media dan Teknologi Pendidikan, 2026)
Low levels of critical thinking skills and scientific literacy among junior high school students highlight the need for innovative and integrative learning approaches. This study aimed to examine the effectiveness of integrating Science, Technology, Engineering, and Mathematics (STEM) within the Project-Based Learning (PjBL) model in improving students’ critical thinking skills and scientific literacy. A quasi-experimental method with a pretest–posttest control group design was employed involving 32 ninth-grade students of RK Makmur Private Junior High School, Medan, divided into an experimental group (n = 16) and a control group (n = 16). The learning intervention was conducted through a project entitled “Smart Eco-Bottle: Water Sensor-Based Plastic Bottle Recycling,” integrating STEM concepts. Data were collected using critical thinking tests (α = 0.82), scientific literacy tests (α = 0.79), observation sheets, and students’ reflections, and analyzed using t-tests and normalized gain (N-gain). The results showed that the experimental group experienced significantly higher improvements in critical thinking skills (N-gain = 0.68, medium) and scientific literacy (N-gain = 0.71, high) compared to the control group (N-gain = 0.24 and 0.22, low; p < 0.05). The novelty of this study lies in the implementation of locally contextualized STEM-PjBL integrated with digital project dissemination through Canva Edu and a YouTube Classroom Channel to enhance students’ digital literacy.